18‐31 GHz GaN wideband low noise amplifier (LNA) using a 0.1 μm T‐gate high electron mobility transistor (HEMT) process. Issue 8 (28th August 2018) - Tong, Xiaodong; Zhang, Shiyong; Xu, Jianxing; Zheng, Penghui; Shi, Xiangyang; Huang, Yang; Wang, Qiyu; Luo, Liwei
Abstract: GaN technology has attracted main attention towards its application to high‐power amplifier. Most recently, noise performance of GaN device has also won acceptance. Compared with GaAs low noise amplifier (LNA), GaN LNA has a unique superiority on power handling. In this work, we report a wideband Silicon‐substrate GaN MMIC LNA operating in 18‐31 GHz frequency range using a commercial 0.1 μm T‐Gate high electron mobility transistor process (OMMIC D01GH). The GaN MMIC LNA has an average noise figure of 1.43 dB over the band and a minimum value of 1.27 dB at 23.2 GHz, which can compete with GaAs and InP MMIC LNA. The small‐signal gain is between 22 and 25 dB across the band, the input and output return losses of the MMIC are less than −10 dB. The P1dB and OIP3 are at 17 dBm and 28 dBm level. The four‐stage MMIC is 2.3 × 1.0 mm 2 in area and consumes 280 mW DC power. Compared with GaAs and InP LNA, the GaN MMIC LNA in this work exhibits a comparative noise figure with higher linearity and power handling ability.